Análise da frequência anual das condições de céu em Botucatu, São Paulo - Teramoto, Erico T. [UNESP]; Escobedo, João Francisco [UNESP] (Universidade Federal da Paraíba (UFPB) Ccsa, 2012)
This paper presents an analysis of the frequency of the sky conditions in Botucatu. The classification of sky conditions was made based on the clearness index (K T), calculated from a database with 10 years of measured daily global solar radiation. Throughout the year in Botucatu, there is a predominance of days with clear sky condition, on average 114 days. For cloudy sky condition, the average frequency is 61 days. About the two intermediate sky conditions, the frequency of the sky partially cloudy with dominance for the diffuse is 94 days and the one with dominance for the clear is 96 days. The main influential factors on the sky conditions in Botucatu are the inputs of cold fronts and the formation of the South Atlantic Convergence Zone. They respond primarily by altering the sky condition of clear to cloudy or partially cloudy with dominance to diffuse. The aerosols resulting from burning in sugarcane fields respond by altering the sky condition from clear to partly cloudy with dominance for the clear.
Analysis of the annual frequency of the sky conditions in Botucatu, São Paulo
Keywords: solar radiation; cloudiness; clearness index